2016
DOI: 10.1016/j.bjp.2016.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic composition, antioxidant and anti-proliferative activities of edible and medicinal plants from the Peruvian Amazon

Abstract: Among 23 extracts of medicinal and edible plants tested, Mauritia flexuosa L.f., Arecaceae, showed significant antioxidant ability (DPPH and ORAC = 1062.9 and 645.9 +/- 51.4 mu g TE/mg extract, respectively), while Annona montana Macfad., Annonaceae, demonstrated the most promising anti-proliferative effect (IC50 for Hep-G2 and HT-29 = 2.7 and 9.0 mu g/ml, respectively). However, combinatory antioxidant/anti-proliferative effect was only detected in Oenocarpus bataua Mart., Arecaceae (DPPH = 903.8 and ORAC = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 39 publications
4
24
0
4
Order By: Relevance
“…Table 3 shows the phenolic compounds present in the buriti pulp. Some phenolic compounds of this fruit [20] such as syringic acid, protocatechuic acid, catechin and ferulic acid present antimicrobial activity as reported by various authors [21 -24]. In this way, the variables studied correlate with the phenolic content and with the antimicrobial activity.…”
Section: Discussionsupporting
confidence: 60%
“…Table 3 shows the phenolic compounds present in the buriti pulp. Some phenolic compounds of this fruit [20] such as syringic acid, protocatechuic acid, catechin and ferulic acid present antimicrobial activity as reported by various authors [21 -24]. In this way, the variables studied correlate with the phenolic content and with the antimicrobial activity.…”
Section: Discussionsupporting
confidence: 60%
“…Excessive iron accumulation can induce significant toxicity both by generation of reactive oxygen species and because of the lack iron excretion regulation in humans ( Nurchi et al, 2016 ). Previous studies have shown the correlation between phenolic compounds and antioxidant activity, in addition to associating the chelating activity of natural products with their composition in the samples ( Loizzo et al, 2012 ; Koolen et al, 2013 ; Cândido, Silva & Agostini-Costa, 2015 ; Tauchen et al, 2016 ). In fact, the structure of phenolic compounds, such as phenolic acids and flavonoids, is decisive for radical elimination and metal chelating activities.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorogenic acid (MM = 354, C 16 H 18 O 9 , Table 1 ), showed signals at 355 [M + H] + , 353 [M − H] − , 162 [caffeic acid], 190 [quinic acid]. It had already been isolated in fruit of Gardenia jasminoides Ellis (Rubiaceae) [ 31 , 34 ], but the first time is described in the Genipa genus.…”
Section: Resultsmentioning
confidence: 99%